Dynamics of Local Leaders' Role in Community Education Development: A Phenomenological Analysis - Marjoni, Mhd Riza (PT. Riset Press International, 2025)
Community education development requires the active involvement of local leaders who understand the social, cultural and potential context of their areas. However, the dynamics of the role of local leaders are often not revealed in depth, especially in facing challenges and opportunities at the community level. This study aims to comprehensively uncover the roles and strategies of local leaders in developing community education. The research approach used a qualitative method with a phenomenological analysis design. Data were collected through in-depth interviews, participatory observation and documentation studies with local leaders, community leaders and community education program managers. Data analysis was conducted through the stages of reduction, presentation and conclusion drawing, with data validity tested through triangulation of sources and techniques. The results show that local leaders play the role of mobilizers, facilitators, mediators and innovators in the development of community education. The success of these roles is influenced by the ability to build trust, optimise social capital and integrate local wisdom in education programs. The main challenges faced include limited resources, resistance to change and limited policy support. However, adaptive and collaborative strategies can overcome these obstacles. In conclusion, the dynamic and adaptive role of local leaders is a key factor in the success of community-based education. Future research is recommended to explore collaborative leadership models across regions to expand the impact of community education development.